User stateless privacy-preserving TPA auditing scheme for cloud storage. (1st March 2019) - Zhao, Haichun; Yao, Xuanxia; Zheng, Xuefeng; Qiu, Tie; Ning, Huansheng
Abstract: In recent years, researchers have proposed some privacy-preserving public auditing schemes to remotely check the integrity of the outsourced data in cloud storage based on the homomorphic authenticators, random blocks sampling and random masking techniques. However, users need to maintain a table related to the block index in almost all of these schemes. It is difficult for users to maintain the table, especially when the outsourced data is frequently updated. To deal with it, a user stateless privacy-preserving public auditing scheme is put forward on rank-based authenticated skip list, which can support dynamical operations completely and makes it unnecessary for users to maintain the relevant table. When the server receives the data originally stored by the user or the user performs dynamic operations on its outsourced data, the server provide users with a time-stamped receipt signed by the both parties. The receipt can not only protect the cloud server from being extorted by the dishonest user, but also ensure that the cloud server update the user's data as required. A formal security proof for data integrity guarantee and an analysis for privacy-preserving property are made in the auditing phase to show the correctness of the scheme. The performance analysis indicates that our interactive audit protocol is with high efficiency.